PERBANDINGAN SIMAYANG TIPE-II DENGAN DISCOVERY LEARNING TERHADAP KEMAMPUAN METAKOGNISI DAN PENGUASAAN KONSEP - Tugiyah Tugiyah; Sunyono Sunyono; Tasviri Efkar (Universitas Lampung, 2015)
The research aimed to compare between the SiMaYang type II learning model and discovery learning to improve metacognition ability and concept mastery has been done. This research used non equivalent control group design in which the 10th grade-2 and the 10th grade-12 was chose as research sample based on cluster random sampling. The results showed that the average n-Gain of metacognitions ability and concept mastery for the 10th grade-2 have